Przyszłość starości. Książka w aktywizacji seniorów - Matras-Mastalerz, Wanda (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2010)
The future of old age: books in activating senior citizens In Poland, 12 million citizens are over 50 years old, which is nearly one third of the country’s population. Therefore activating senior citizens becomes an important issue. The question that arises is: how to make the awareness of the old age a source of pride and joy instead of a burden? It cannot be claimed that there is a simple correspondence between people’s age and their physical, psychic and social activity. Some of the senior citizens are “forever young”: full of energy, vigorous, following their ever-new interests and passions, curious of the world, smiling and active. What factors influence their vitality and provides them with energy? An important role in stimulating the mental activity of senior citizens is played by their contact with the book. Reading exercises memory, allows us to retain mental abilities in good shape until old age, and has self-educational function. Reading activates the parts of brain responsible for information reception and processing and for imagination. Directed reading provides patterns of behaviour and often helps in identifying the sense and goal of life. Reading provides strength to find oneself in a new, sometimes challenging situation, and may help to activate a sick, lonely, or withdrawn person. It allows us to understand ourselves and others better, enriches emotional life, enables “insights into oneself”, and satisfies aesthetical needs, according to the Chinese proverb: “a book is like a garden carried in your pocket”.